A combined numerical approach for the thermal analysis of a piston water pump. (November 2020) - Milani, M.; Montorsi, L.; Venturelli, M.
Highlights: Development of a new CFD approach to model high pressure water piston pumps. Multi-phase modelling for the lubrication and cooling effects for crankcase region. Experimental and numerical analysis of the thermal behaviour of the pump. Friction and thermal losses can be predicted to enhance pump efficiency. Abstract: The paper proposes a numerical model for the investigation of a piston water pump under different operating conditions. In particular, the lubricating system is analysed and modelled. The study accounts for the lubrication and friction phenomena, heat transfer, multiphase fluid approach and motion simulation. A computational thermo fluid dynamics approach has been adopted to develop a numerical tool able to simulate the behaviour of the oil during the machine working phases. The CFD approach simulates the moving metal components by means of moving meshes techniques; the friction phenomenon is estimated on the basis of formulations available in literature. The numerical model evaluates the heat transfer between moving metal parts and oil during the operating phases of the system. Furthermore, the heat transfer between oil and environment is calculated, accounting for conduction through the metal crankcase walls. A multiphase fluid approach is used for the simulation of the oil and air mixing during the crank rotation. The heat transfer coefficient predicted by the CFD approach are employed in a lumped and distributed numerical model; the reliability and accuracy of the proposed numerical approach is addressed and validated against experimental results. Experimental data have been collected by means of a thermographic camera and thermocouples. Finally, the tool's predictive capabilities are addressed by simulating different working conditions.